Changes of knowledge, attitudes, beliefs, and preference of bar owner and staff in response to a smoke-free bar law. Issue 1 (25th February 2004) - Tang, H; Cowling, D W; Stevens, C M; Lloyd, J C
Abstract : Objective: To examine attitudinal changes of bar owners and staff regarding a smoke-free bar law. Design: Bar owners and staff were random selected and telephone interviewed in June 1998, shortly after a smoke-free bar law was enacted, and October 2002. Similar instruments were used in both surveys to collect data on attitudes related to secondhand smoke (SHS) and behaviours related to the smoke-free bar law. Participants: 651 and 650 respondents worked for either stand alone bars or combination bars. Measures: Preference of working in a smoke-free environment, concerns of the effect of SHS, and how to comply with the law. Results: The percentage of bar owners or staff working in stand alone bars who prefer to work in a smoke-free environment increased from 17.3% in 1998 to 50.9% in 2002 (p < 0.001). Significantly more respondents (45.5%) working in stand alone bars were concerned about the effects of SHS on their health, comparing to 21.6% in 1998 (p < 0.001). When patrons smoked in the bar, 82.1% of stand alone bar owners or staff in the 2002 survey would ask them to stop or to smoke outside, increased from only 43.0% in the 1998 survey (p < 0.001). Conclusion: A positive and significant attitudinal change related to the smoke-free bar law occurred among California bars.